Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to know the general formula for $\sum_{n=0}^{m}nr^n$ for some constant r and how it is derived.

For example, when r = 2, the formula is given by: $\sum_{n=0}^{m}n2^n = 2(m2^m - 2^m +1)$ according to http://www.wolframalpha.com/input/?i=partial+sum+of+n+2%5En

Thanks!

share|improve this question
    
Certainly asked here several times. Can't find a link right now. –  lhf Mar 13 '12 at 11:22
    
Brilliant answers from everyone. thank you all so much –  hollow7 Mar 16 '12 at 13:08
    
@dragoncharmer Either you tag this [algebra-precalculus] or you tag it [taylor-expansion]. Those are quite mutually exclusive tags. –  Pedro Tamaroff May 2 '12 at 1:46

4 Answers 4

up vote 3 down vote accepted

I see that one of the tags is pre-calculus, so here is a way to answer the question that does not use differentiation:

$S = r + 2r^2 +3r^3 +\dots + (m-1)r^{m-1}+mr^m $
$rS = \ \ \ \ r^2 +2r^3 +\dots + (m-2)r^{m-1}+(m-1)r^m + mr^{m+1} $

Subtracting the bottom line from the top, we get
$$(1-r)S = r+r^2 +r^3 + \dots + r^{m-1} + r^m -mr^{m+1} .$$ But using the formula for the sum of a geometric series, we have that $$(1-r)S = \frac{r(1-r^m)}{1-r} -mr^{m+1}.$$ Dividing by $(1-r)$, we have $$ S=\frac{r(1-r^m)}{(1-r)^2} -\frac{mr^{m+1}}{1-r}. $$ (Obviously, for this to hold, one needs $r \neq 1$. If $r=1$, then we are looking at $\sum_{n=1}^m n= \frac{m(m+1)}{2}$.)

share|improve this answer

Hint:

  • The Geometric series...

  • Differentiation.

share|improve this answer

I suppose you are familiar with the sum of an arithmetic progression: $$ 1+x+x^2+\dots+x^m=\frac{x^{m+1}-1}{x-1}. $$ Take derivatives an multiply by $x$.

share|improve this answer
    
Typo: sum of Geometric progression –  Learner Mar 14 '12 at 16:07

Observe that your formula $\sum_{n=0}^{m}nr^n$ can be obtained from $\sum_{n=0}^{m}x^n$ by applying $x\frac d{dx}$ (deriving and then multiplying by $x$) and then substituting $r$ for $x$. Now for geometric series one has the well known formula $$ \sum_{n=0}^mx^n=\frac{x^0-x^{m+1}}{1-x} $$ and applying $x\frac d{dx}$ to the right hand side gives $$ \frac{x-(m+1)x^{m+1}+mx^{m+2}}{(1-x)^2} = x\frac{1-x^m+mx^m(x-1)}{(1-x)^2} =x\left(\frac{1-x^m}{(1-x)^2}-\frac{mx^m}{1-x}\right) $$ so that your answer should be $$ \sum_{n=0}^{m}nr^n=r\left(\frac{1-r^m}{(1-r)^2}-\frac{mr^m}{1-r}\right). $$ For $r=2$ this gives $2(1+(m-1)2^m)$, in accordance with what you found.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.